2022
DOI: 10.33308/2687248x.202243273
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 hastalığı tanısı alan hastalarda belirsizliğe tahammülsüzlük ve ölüm kaygısı

Abstract: Amaç: Covid-19 hastalığının hızla yayılması, yüksek ölüm oranı ile seyretmesi, etkin tedavisinin olmaması ve bilgi eksikliği, insanlarda belirsizlik duygusunun artmasına ve ölüm korkusuna sebep olmuştur. Bu çalışmanın amacı Covid-19 tanısı olan hastalarda belirsizliğe tahammülsüzlük ve ölüm kaygısı düzeylerini değerlendirmek ve bu değişkenler arasındaki ilişkiyi belirlemektir. Yöntem: Temmuz- Ağustos 2021 tarihleri aralığında İstanbul’da bir hastanede Covid-19 tanısıyla izolasyon servislerinde yatmakta olan 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In this study, although the fear of death was higher in the vaccinated group than in the non-vaccinated group, it was not statistically significant. Turhan and Boyacıoğlu reported that hospitalization increased death anxiety in COVID-19 [30]. In the literature, it is reported that people with intrinsic religious motivation have lower death anxiety [31].…”
Section: Discussionmentioning
confidence: 97%
“…In this study, although the fear of death was higher in the vaccinated group than in the non-vaccinated group, it was not statistically significant. Turhan and Boyacıoğlu reported that hospitalization increased death anxiety in COVID-19 [30]. In the literature, it is reported that people with intrinsic religious motivation have lower death anxiety [31].…”
Section: Discussionmentioning
confidence: 97%